GOVERNMENT’S FEAR OF NEWSPAPERS IN RUSSIA AND FRANCE IN THE SECOND HALF OF THE 19TH CENTURY - V. F. Blokhin (Vestnik MGIMO-Universiteta)
The article is devoted to one of the measures of administrative influence on the publishers of periodicals in the form of a ban on the retail sale of newspapers and magazines in the imperial Russia and France. The author argues that this policy was introduced in Russia due to adoption of foreign experience of direct and indirect censorship, especially the French experience. So, the article seeks to access the difference between the original approach of the French empire and the Russian version of the policy. Also the article bridges the gap between the current Russian historiography and the existing archive materials with help of discourse analysis and comparative method. First, the author reviews the literature on Russian and French censorship in the second half of XIX century. This allows us to describe the original policy motives of leadership in France in area of media coverage and censorship. Second, the author presents some comparative parallels in the particular area of study of censorship and its institutional basis. Using official documents, data on discussions of the alleged measures and the reasons for their introduction, author shows features of approaches of the Russian Ministry of internal Affairs and a member of his censorship Departmen t to highligh t the key issues of social development, to enhance the effectiveness of state censorship policy. The article gives the significant boost towards new approaches in research of indirect censorship in Russia and France as well as the role models for such a policy. Also the article allows us to reconsider the diffusionist paradigm with regard to state's policy experience circulation between European empires and their reaction to the emergence of modern media.